Philosophical Study of the Local Wisdom of “Guni Gelo” as Restorative Justice in Customary Law in Kangae District, Sikka Regency, NTT Province - Micael Josviranto; Yoseph Darius Purnama Rangga; Agustino Resen Wakhe (Dinasti Research, 2024)
The Issue of law is one that directly touches human life. One of the legal systems closely tied to humans since ancient times is customary law, which has developed orally. In Kangae District, Sikka Regency, there is a customary law term known as